Factores asociados al nivel de liderazgo en estudiantes de enfermería de la Universidad Nacional de la Amazonía Peruana, Iquitos 2022 - Panaifo Lovera, Janet (2024)
The objective was to determine the factors associated with the level of leadership in Nursing students, from the National University of the Peruvian Amazon, Iquitos 2022. To do this, the quantitative method was used, through a non-experimental, descriptive, cross-sectional and correlational design. A population of 297 students from the Faculty of Nursing of the National University of the Peruvian Amazon was used. The sample was 168 students calculated using the formula for finite populations. In data collection, the technique was the survey and the instruments were: Data sheet on personal, family and academic factors and leadership level questionnaire. For the bivariate analysis, Pearson's X2 test was used. The results obtained were: 48.8% are between 17 and 19 years old, 78% are female, 79.2% belong to an urban area, 50% have a family income less than or equal to 930 soles, 82.1% live with their parents, 29.8% are in the first level of education, 55.4% have an average academic performance, 86.3% did not belong to study groups and 78.6% have a level leadership level. The work concludes that there is an association between the level of leadership in Nursing students with age (p= 0.000), sex (p = 0.021), place of residence (p = 0.014), family economic income (p = 0.024), living with parents (p = 0.025), educational level (p = 0.035), academic performance (p = 0.007) and membership in study groups (p = 0.015).